2007
DOI: 10.1002/jssc.200700236
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mixture design – principal component optimization for selective compound extraction from plant material

Abstract: A simplex centroid design is used to optimize solvent mixtures for selective extraction of compounds from Erythrina speciosa Andrews leaves. Three main groups of compounds characterized by chromatographic retention times of 1.7, 3.1, and 6.6 min were extracted. The chromatographic peak heights registered at 1407 equally spaced times for each design extract were converted into principal components (PCs). Three PCs account for 89.1% of the data variance and have important loading values at the above retention ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
(8 reference statements)
1
13
0
1
Order By: Relevance
“…These results show some similarity with the results obtained from our previous work [9,10]. There, we analyzed the crude extracts by HPLC and the data were subjected to principal component and varimax analysis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results show some similarity with the results obtained from our previous work [9,10]. There, we analyzed the crude extracts by HPLC and the data were subjected to principal component and varimax analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Recently our group has shown that statistical mixture designs permit the development of rigorous but economical procedures for demonstrating the effects of solvent changes on the extracted constituents of plant material [9,10]. Experiments were carried out using mixtures of solvents that have been chosen using statistical criteria to minimize modeling error as well as reduce the number of experiments that must be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Além de seu extensivo uso na análise exploratória de matrizes, tais como solos, 10,11 plantas 12 e alimentos, 13 a PCA também encontrou aplicação recente no planejamento e otimização de misturas. [14][15][16] Neste trabalho, a PCA foi usada para se obter uma visão sintética e global dos planejamentos experimentais, a fim de se decidir pelas melhores condições de análise. As condições ótimas serão usadas na análise de uma amostra de braquiária fornecida pelo PIATV, 1 para a qual foram determinados os sete elementos químicos.…”
Section: Introductionunclassified
“…The choice of extraction solvent can be made by appropriate statistical mixture designs. 17 UV-Vis and infrared spectroscopic analytical techniques have been used in the identification and quantification of metabolome constituents in coffee. Sample preparation is relatively simple and the reagents and equipment are not very expensive.…”
Section: Introductionmentioning
confidence: 99%